Molecular epidemiology of SEN virus among blood donors and renal dialysis patients - Almaqati, Thekra; Elnagi , Elmoeiz A.; Al Zahrani , Faisal; Muzaheed; Mohammed , Zeinab S.; Alomar , Amer; George , Siju K; Jacob, Ashly Mary; Mashwal, Fahad A (Acta Biomedica Atenei Parmensis, 2022)
Background and purpose: The SEN virus (SEN-V) is a single-stranded circular, non-enveloped DNA virus that has been linked to blood transfusion and is thought to be a major cause of post-transfusion hepatitis. The two SENV types, SENV-H and SENV-D, are non-A to E hepatitis viruses  in those who are infected. The purpose of this study is to find out how common SENV and its variations are among renal dialysis patients and healthy blood donors.Methods: The study used a cross-sectional design, with 300 blood samples collected from KFMMC patients, 150 from healthy blood donors and 150 from renal dialysis patients, between January 2019 and January 2021. The samples were screened for the presence of SENV-D and SENV-H. using nested PCR.Results: Molecular analysis of the SEN virus revealed that 9.3% of the samples (14 out of 150) tested positive for SEN virus infection in renal dialysis patients. The data from healthy donors revealed that 10% of the samples tested positive for the SEN virus (15 out of 150).Conclusions: The presence of SEN-V in healthy blood donors and renal dialysis patients demonstrates the virus's blood-borne nature and emphasizes the dangers of blood-borne transmission.